Компромисс в праве и правовой компромисс - Некига, С. Н.; Некига, С. Н.; Nekiga, S. (My University, 2012)
The article defi nes the concept of a legal compromise and compromise in the law. Making the analysis of the compromise as a priority area for development in the fi eld of jurisprudence. The author outlines the specifi c requirements of compromise and limits of it’s admissibility.
Некига С. Н. Компромисс в праве и правовой компромисс / С. Н. Некига // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред..), Л. І. Кормич (заст. голов. ред..), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України ; НУ ОЮА. – Одеса : Фенікс, 2012. – Вип.. 45. – С. 59-65.
Keywords: правовой компромисс; компромисс в праве; требования применения компромисса; границы допустимости; правовий компроміс; компроміс у праві; вимоги застосування компромісу; межі допустимості; legal compromise; the right compromise; demands the use of compromise; Acceptance levels